(untitled) (Architecture Image Studies, 2026)
Rapid changes in the business environment require organizations to adopt a structured change management model in order to adapt effectively and develop more competitive business models. However, a comprehensive framework that systematically maps key transformation factors and prioritizes strategic elements with the greatest influence on change success remains limited. This study aims to design a change management model that strengthens the competitive advantage of Islamic life insurance companies. The research employs a qualitative method with a quantitative approach. Data were collected through literature review, questionnaires, interviews, and Focus Group Discussions (FGDs). Data analysis was conducted using descriptive analysis. The findings indicate that the success of change management is strongly influenced by transformational leadership, digital technology adoption, enhancement of human resource quality, and product innovation, thereby enabling the development of business models that are more adaptive, efficient, and competitive.